Analisis Nilai Budaya dan Nilai Kepahlawanan pada Buku Romusa Sejarah yang Terlupakan Karya Hendri F. Isnaeni dan Apid Sebagai Bahan Pembelajaran Bahasa Indonesia Berbasis TPACK di SMA - Maesaroh, Liyana (Universitas Mathla'ul Anwar Banten, 2024)
This research aims to describe the cultural values ​​and heroic values ​​in the forgotten historical romance book by Hendri F. Isnaeni and Apid to be used as TPACK-based Indonesian language learning material in high school. This research uses a qualitative descriptive type or approach, literature study methods and content analysis techniques. The steps used by researchers in collecting data are as follows: (1) outline the parts that are considered important, (2) select the data, (3) provide a description, (4) draw conclusions. Based on the results of the analysis of forty-eight quotations in the book Romusa's forgotten history by Hendri F. Isnaeni and Apid, the following conclusion was obtained: the cultural value of human relations with God which is described as piety, love of prayer, and surrender to God is not found in history books the. Human relationships with other humans are described by helping each other in 7 quotes and sincerity in 1 quote. The relationship between humans and nature is described by using the environment with 5 quotes and loving the environment with 1 quote. The human relationship with oneself is described with 3 quotes of honesty, 2 quotes of persistence, and 1 quote of self-determination. The value of heroism includes the value of courage which is described by the strength that exists in each person's soul in 1 quote, fighting for something in 5 quotes, and being brave in 1 quote. The value of optimism is described by 5 quotes about thinking patterns, 5 quotes about being realistic in seeing a problem, and 3 quotes about having hope. The value of never giving up is described seriously in 1 quote and strong determination in 5 quotes. The value of solidarity is described by loyal friends who are not available, and helping people in need in 1 quote. The value of being willing to sacrifice is described with sincerity in 1 quote. The forty-eight quotes in the book Romusa's forgotten history by Hendri F. Isnaeni and Apid can be used as TPACK-based Indonesian language learning material in high school. The book can be studied for its cultural and heroic values ​​and the book is included in the historical story.